Effect of Coal with High Moisture Content on Boiler Operation Parameters at Thermal Coal Fired Power Plant - S. Salmi, A.A. Nuraini (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Focus on developing county, the electricity industry plays important roles. In fact, energy drives the national growth in supporting the other industries. Most developing country produce electrical energy through thermal coal plant and is recorded above 70 percent of total Asian capacity. Coal is still a choice as the main fuel in thermal coal plant due to cheaper price compared to another type of fuel, distillate or gas. However, coal performance is uncertain due to the different characteristics and coal types. Coal must be tested and analyzed before fired into the boiler. Problematic coal may cause issued to the boiler furnace such as ash slagging and fouling, ash corrosion, tube leak, and consequently impacts to the boiler efficiency. Therefore, this study purposely to investigate the effects of sticky coal on the boiler operation parameters. The study found boiler pressure deviation was fluctuated badly to minus 25bar, coal flowrate was decreased to minus 5 tonnes per hour during firing coal with high moisture content. By looking at pulverizer parameters, mill different pressure at bowl was decreasing, mill motor current was increased about 5 Amps and primary air to carry the pulverized fuel increased accordingly. From this study, the main factor of sticky coal is due to high moisture contents. Hence, to minimize the high moisture contents, coal not recommended to remain in the yard for a long time.